2019
DOI: 10.1108/lodj-01-2019-0026
|View full text |Cite
|
Sign up to set email alerts
|

Authentic leadership and employee performance: mediating role of organizational commitment

Abstract: Purpose The purpose of this paper is to investigate the effect of authentic leadership (AL) on employee performance (EP) and to examine the mediating role of organizational commitment (OC). Design/methodology/approach Data were obtained from all employees (216) of tourism agencies in Guilan province (Iran) using a 19-item survey. In total, 173 questionnaires were returned, yielding a response rate of 80 percent. A mediation model was outlined and tested using structural equation modeling. Findings The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 46 publications
6
54
0
2
Order By: Relevance
“…The respondents see their bosses leading with t ransparency, with h igh moral values that translate into their actions and decisions, with fairnes s in treating their subordinates, and with a clear sense of their own strengths and weaknesses, which affect their intention to remain co mmitted to the organization. The results coincide with a number of studies previously discussed, which established the positive effect of authentic leadership to o rganizat ional commit ment (Roncesvalles & Gaerlan, 2020;Rego, Lopes & Nascimento, 2016;Albashiti, Hajjaj & Thabet, 2017;Gat ling, Kang & Kim, 2016;Hadian Nasab & Afshari, 2019;Hlongwane & Olivier, 2017;Sunga, 2020).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The respondents see their bosses leading with t ransparency, with h igh moral values that translate into their actions and decisions, with fairnes s in treating their subordinates, and with a clear sense of their own strengths and weaknesses, which affect their intention to remain co mmitted to the organization. The results coincide with a number of studies previously discussed, which established the positive effect of authentic leadership to o rganizat ional commit ment (Roncesvalles & Gaerlan, 2020;Rego, Lopes & Nascimento, 2016;Albashiti, Hajjaj & Thabet, 2017;Gat ling, Kang & Kim, 2016;Hadian Nasab & Afshari, 2019;Hlongwane & Olivier, 2017;Sunga, 2020).…”
Section: Resultssupporting
confidence: 89%
“…Findings showed that the perceptions of their leaders or managers" authentic leadership positively affect both employee performance and organizational commit ment. There is likewise a significant relationship between authentic leadership and emp loyee performance, which is positively mediated by organizational commitment (Hadian Nasab & Afshari, 2019).…”
Section: Introductionmentioning
confidence: 93%
“…Employees' job performance can be affected by many factors. When reviewing the studies in the literature, factors such as job satisfaction [28][29], organizational commitment [30], organizational citizenship behavior [31], perceived organization support [32][33], organizational trust [34], motivation [35], perception of ethical leadership [36] affect the employees' job performance in positive manner. Whereas factors such as work overload [31], organizational cynicism [37][38], mobbing [39] affect the employees' job performance negatively.…”
Section: Employees' Job Performancementioning
confidence: 99%
“…A plethora of studies have acknowledged that authentic leadership can bring multi-faceted outcomes for an organization such as improved organizational commitment [22,23], organizational citizenship behavior [24,25], employee performance [26], employee engagement [27], etc. However, it is not clear in the prior literature how authentic leadership can be related to inducing workplace innovative behavior of the employees.…”
Section: Introductionmentioning
confidence: 99%